Effect of Mycorrhizal Inoculation and Pre-treatment with Salicylic Acid at Different Levels of Drought on Morphological Traits and Yield of Flax - A. Ansari; J. Razmjoo; H. Karimmojeni; M. Zarei (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2014)
The use of plant growth hormones and beneficial microorganisms, could reduce the drought damage. The purpose of this study was to investigate the treatment with salicylic acid and inoculated with mycorrhizal fungi at different levels of irrigation on flax growth. A factorial experiment based on randomized complete blocks design with 3 replications was performed in growth chamber of college of agriculture, Isfahan university of technology and in the years 2010-2011. Treatments were irrigation regimes at 3 levels (100%, 70% and 40% field capacity), mycorrhizae at 3 levels (non-inoculated and inoculated with two species Glomus mosseae and G. intraradices) and salicylic acid in 2 levels (seeds treated with 250 μM concentration of salicylic acid for 8 hours and non-treated seeds). The level of 40% field capacity irrigation reduced the leaf number, root length, root dry weight, height, stem and leaf and total plant dry weight, number and weight of capsules per plant, number of seeds per capsule and seed yield and increased vesicle diameter and percent colonization. Both mycorrhizal species in the three levels of irrigation increased the drought tolerance of the flax but in G. mosseae was more effective. Salicylic acid decreased some of the investigated traits. Inoculation with mycorrhiza and treatment with salicylic acid reduced the investigated characteristics than the inoculation with mycorrhiza and non-application of salicylic acid. 100% field capacity and G. mosseae species were the best irrigation level and mycorrhizal fungi respectively. Therefore it is suggest that application of mycorrhizal fungi especially G. mosseae species increase in the cultivation of flax plants without treatment with salicylic acid, especially in drought conditions because in addition to increased yield, water consumption is also lower and it makes the plant more tolerant to stress conditions such as drought.